The many adventures of Winnie the Pooh [videorecording (DVD)] - Lounsbery, John; Reitherman, Wolfgang, 1909-1985; Walmsley, Jon; Cabot, Sebastian; Winchell, Paul; Holloway, Sterling; Matthews, Junius, 1890-1978; Milne, A. A. (Alan Alexander), 1882-1956 (Disney DVD., 2013)
Experience the very first time Tigger "pounces" Pooh; laugh out loud when Pooh's rumbly tumbly gets him stuck in a hilariously sticky situation. All your favorite Hundred Acre Wood characters come alive in this timeless motion picture overflowing with rich animation, masterful storytelling, and unforgettable songs. Share all the fun, whimsy, and wonder in this special edition of the original Disney classic, digitally restored and remastered in high definition to thrill a whole new generation!